Tumor-to-tumor Metastases: Papillary Renal Cell Carcinoma into A Papillary Thyroid Carcinoma: A Case Report - Paul, Shrebash; Hannan, Tabiha Binte; Begum, Julekha; Rahman, SM Mahbubur; Sikder, Istiaque Ahmed; Rahman, Wahida; Chowdhury, Fazle Rabbi (Journal of Medicine, 2022)
Thyroid malignancies are commonest endocrine malignancy. It can be primary, can be secondary also.Though secondary thyroid malignancies are rare it happens sporadically from kidney, skin, breast andhead-neck tumor. Here we described a case of metastatic papillary thyroid carcinoma. This case wasdiagnosed as a case of papillary cell carcinoma of left kidney 18 months back, underwent radical nephrectomyand received a course of Tyrosine Kinase Inhibitor also and remain symptom free for one year. Thenpresented to us with thyroid swelling along with cervical lymphadenopathy. J MEDICINE 2022; 23: 77-81